Intervenciones no farmacológicas en el rol de enfermería para el manejo del dolor en paciente oncológico adulto mayor - Miranda Miranda, Jennifer Lissette (2025)
Introduction: Pain in oncology patients can be presented in a variety of ways, and is a challenge for nursing professionals. The nursing professional plays a key role in performing nonpharmacologic interventions for pain management in the older adult cancer patient. Objective: To identify the role of nursing in non - pharmacological interventions for pain management in the older adult cancer patient, through a systematic review of the literature. Materials and methods: A qualitative and non - experimental narrative review with a cross - sectional approach was carried out. The search for information was done in indexed databases such as PubMed and Scielo, using PICO and PRISMA strategies, prioritizing studies since 2019. Twenty relevant articles were included and non - indexed sources and bibliographies with incomplete information were excluded. Results: The findings confirmed that the nurse plays a fundamental role in the implementation of noninvasive pain management interventions to help meet patients' health needs, which should be patient - centered. In addition, the personal benefits that were appreciated in the improvement before life are the emotional state and better coping with the disease. Conclusions: The attention of nursing staff is fundamental to perform non - pharmacological methods, employing adjuvant actions of pharmacological treatment in the management of oncologic pain. In the future, research is needed on interactions for pain management with complementary therapies without work overload, being fundamental for the well - being and improvement of the patient.